A Systematic Review on the Therapeutic Effects of Ayahuasca - Joana Gonçalves; Ângelo Luís; Eugenia Gallardo; Ana Paula Duarte (Plants, 2023)
Traditional therapies, resorting to the use of plants, have acquired a great demand over the years, both for economic reasons and the preference for natural treatments. Some studies suggest that ayahuasca may have beneficial properties in treating some physical and psychological imbalances. Thus, we carried out a systematic review of studies published up to December 2022, where these themes were addressed. The search was carried out in the PubMed database, and only studies written in English and published in peer-reviewed journals were included. Thus, 228 publications were identified, of which 66 were included in the present study. The reviewed studies suggest that ayahuasca may have beneficial effects on various physical and psychological conditions, namely in the treatment of depression, anxiety and various diseases of the neurobiological system, as well as anti-inflammatory and antimicrobial properties, demonstrating its therapeutic potential. The number of studies that address this issue has also been growing, demonstrating interest in the search for alternative treatments. However, to the best of our knowledge, this is the first systematic review where all the findings of therapeutic effects associated with the consumption of ayahuasca are reviewed.